2022
DOI: 10.1111/jan.15436
|View full text |Cite
|
Sign up to set email alerts
|

Self‐report instruments for measuring patient dignity: A psychometric systematic review

Abstract: Aims:To synthesize and evaluate the psychometric properties of self-report instruments that measure patient dignity.Design: A psychometric systematic review. Data sources: A comprehensive search of studies published from inception until February 17, 2022, was performed using PubMed, Embase, CINAHL, Web of Science, and Scopus. Review Methods: The methodological quality of the psychometric studies was evaluated following the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The resulting 15-item PROM with a 5-factor structure covers the major factors that affect hospitalized older adults' dignity as discussed in the literature, including shared decision-making, HCP-patient communication, patient autonomy, patient privacy and respectful care (Kerr et al, 2020;Nouri et al, 2017;Šaňáková & Čáp, 2019;. Previous systematic reviews of dignity-related PROMs have identified the Inpatient Dignity Scale (IPDS) (Ota et al, 2019) and the Patient Dignity Inventory (PDI) (Chochinov et al, 2008) as the most valid and reliable measures for measuring patients' dignity during acute hospitalization (Fuseini, Redley et al, 2023;Lam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The resulting 15-item PROM with a 5-factor structure covers the major factors that affect hospitalized older adults' dignity as discussed in the literature, including shared decision-making, HCP-patient communication, patient autonomy, patient privacy and respectful care (Kerr et al, 2020;Nouri et al, 2017;Šaňáková & Čáp, 2019;. Previous systematic reviews of dignity-related PROMs have identified the Inpatient Dignity Scale (IPDS) (Ota et al, 2019) and the Patient Dignity Inventory (PDI) (Chochinov et al, 2008) as the most valid and reliable measures for measuring patients' dignity during acute hospitalization (Fuseini, Redley et al, 2023;Lam et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…that have not been captured by previous dignity-related measures (Karimi et al, 2019; TA B L E 3 Results of exploratory factor analysis. (Fuseini, Redley et al, 2023;Lam et al, 2022). Another unique contribution of the HOADS to the advancement of knowledge on dignity for older adults is the identification of PROM items that are unique to the Ghanaian and African contexts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations